Frequency of Cardiac Arrhythmias in Hypertensive Patients - Tariq, Muhammad Naeem; Samore, Naseer Ahmed; Rashid, Muhammad Humayoun; Aziz, Sohail; Chaudhery, Ghoza; Ali, Jahanzab; Azad, Naseem; Noeman, Ahmad; Yamin Bukhari, Syeda Neelam; Chaudhry, Azhar Ali (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of cardiac arrhythmias in hypertensive patients. Study Design: Analytical Cross -sectional study. Place & Duration of Study: Tertiary Cardiac Center, Lahore Pakistan from Jan 2021 to Dec2021. Methodology: Two hundred patients (males and females), age between 20-80 years, suffering from hypertensive disease (Blood Pressure ≥ 140/90mmHg), one year before were assessed in the study. After that ECG was done according to International standards. Then patients undergone 24 hour Holter monitoring test. Presence of cardiac arrhythmia was confirmed by the interpretation of 12 lead ECG and 24 hour Holter report. All the data was noted. Patients with cardiac arrhythmias were treated in consultation from the Electrophysiology (EP) department of the hospital. By using the SPSS version 26, the statistical data was tabulated, analyzed and interpreted. Results: The mean age was calculated to be 58.64±7.74 years. In this study the males were 148(74%) while 52(26%) were females. The mean duration of hypertension was found to be 5.09±1.56 years. Cardiac arrhythmias were noted in 22(11%) cases. Out of 22 cases of cardiac arrhythmias, 02(1%) patients had premature atrial contractions, 02(1%) had atrial flutter, 04(2%) had premature ventricular contractions and 14(7%) had atrial fibrillation. Cardiac arrhythmias were significantly higher in patients above 40 years of age (p0.05). Conclusion: The research study concluded that in hypertensive patients, the cardiac arrhythmias frequency is low but its value is not unremarkable.